Interdisciplinary Foundations for Environmental and Sustainability Ethics: An Introduction - Dereniowska, Małgorzata; Matzke, Jason (ETHICS IN PROGRESS, 2014)
This article introduces the special issue for Ethics in Progress entitled Environment, ethics, and sustainability: Crossroads of our future. Despite four decades of intense development in the field of academic and professional environmental ethics, environmental problems pose ever increasing ethical challenges. The discipline continues to undergo a transition from focusing on theoretical questions such as what kinds of beings deserve moral standing toward greater inclusion of the multifaceted dimensions of sustainability and environmental issues and policy formation. In this introductory paper, we present the development, some of the key disciplinary debates, and the continuing and emerging challenges in environmentalism as it intersects with sustainability. We emphasize the importance of increasing the range of interdisciplinary perspectives brought to bear on practical ethics. The papers included in this special issue reflect both the challenges that arise as environmental ethics continues to expand and explore new issues at the intersection of ethics, sustainability, and environmental research, and the interdisciplinarity required in our search to better understand matters related to environmental history, environmental inequalities, social and environmental value conflict, inter-generational justice, and ethical components of the human relationship with the world.